Validitas Alat Praktikum Kimia Berbasis Bahan Bekas pada Materi Termokimia - Cindi Patika Sari; Raudhatul Fadhilah*; Dedeh Kurniasih (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Practicum is often not carried out in schools because of the limitations of practical tools. Therefore, it is necessary to develop practical tools to make it easier for students to understand the concept of thermochemistry. This study aims to produce a valid and practical thermochemistry practicum tool. Validity is measured from the material and media aspects using a validation sheet. Meanwhile, practicality was measured using teacher and student response questionnaires. This type of research is research and development (research and development) ADDIE model (analysis, design, development, implementation, and evaluation). The results of the analysis show that the thermochemical practicum tool developed is declared to be very valid with an average value of 0.94 and 0.92. The results of the practicality test obtained very practical criteria in the initial field trial and the main field trial an average of 94.64% and 97.92%, respectively. Thus, the thermochemistry practicum tool developed is suitable to be used as a medium for learning thermochemical material.